Association between different systemic therapies and the risk of tuberculosis in psoriasis patients: A population‐based study. Issue 12 (15th November 2021) - Ting, Sze‐Wen; Ting, Sze‐Ya; Lin, Yu‐Sheng; Lin, Ming‐Shyan; Kuo, George
Abstract: Background: Despite the evolution of biologic agents, the use of traditional systemic immunosuppressants still account for a considerable proportion of systemic anti‐psoriasis therapy. The risk of tuberculosis among psoriasis patients receiving such conventional immunosuppressants is not clearly understood. Methods and Materials: We used the retrospectively‐collected data from the Taiwan National Health Insurance Research Database to perform this prospective cohort study. We included 94, 585 adult patients with newly diagnosed psoriasis between January 1, 2001 and December 31, 2013. We documented the exposure of systemic anti‐psoriasis therapies. The outcome is incident mycobacterium tuberculosis infection. Results: During a mean 6.8 years follow‐up, 703 (0.74%) incident tuberculosis was diagnosed and treated. The crude incidence of tuberculosis was 1.11 (95% confidence interval [CI] 1.03‐1.19) events per 1000 person‐years. The result demonstrated that MTX (Hazard ratio [HR] 2.16, 95% CI 1.47‐3.16) and tacrolimus (HR 5.31, 95% CI 1.66‐17.01) were significantly associated with increased risks of tuberculosis. Noticeably, azathioprine was a borderline significant risk factor of tacrolimus (HR 2.63, 95% 0.96‐7.21, P = 0.059). The risk of TB in patients receiving adalimumab was twofold (HR 2.07) though not significant because of only one TB event was detected. The steroid was also associated with a dose‐dependent increase of tuberculosis risk (HR 1.09, 95% CI 1.09‐1.12, for every 1 mg of prednisolone equivalent dose per day). Conclusion: The study found that among systemic anti‐psoriasis therapy, methotrexate, tacrolimus, azathioprine and steroid may be associated with an increased risk of tuberculosis.